Local lithic landscapes and local source complexity: Developing a new database for geological sourcing of archaeological stone artefacts in North-Western Australia. (April 2019) - Ditchfield, Kane; Ward, Ingrid
Abstract: Raw material sourcing is critical for not only understanding past mobility and stone technology but also the formation of stone artefact assemblages. Despite this, very little sourcing work has been conducted in Western Australia where stone artefacts dominate the archaeological record. This problem exists partially because of a generally complex local and regional geology. At the same time, in the wider literature, there is also a tendency to focus on sourcing non-local (>10 km) artefacts over local artefacts (<10 km). To exemplify these problems, this paper focuses on raw material sourcing in parts of the coastal Carnarvon and Pilbara, particularly Barrow Island and Cape Range. Both landscapes have long occupation histories (>40 ka). A raw material database of both local and non-local sources is proposed. This database is initially focused on macroscopic, petrographic and some geochemical analysis which can later be extended to include more detailed geochemistry. The first set of results from the database indicate that both limestone and calcrete were sourced locally, while locally available indurated rocks like sandstone have more variable source locations, including the possibility of now-drowned parts of the inner shelf. It is hoped that this study may be translated to other parts of Australia and beyond, where there are similar complexities in sourcing of stone artefacts. Highlights: Geological background for the coastal Carnarvon and Pilbara is reviewed in some detail. A geological sourcing database for stone artefacts is proposed for north-western Australia. Initial results from the database show that the local lithic landscape, and the sources it hosts, is complex. Sourcing local artefacts should be given as much attention as sourcing non-local artefacts.